The Effect of Polyvinyl Chloride (PVC) Microplastic Exposure in Feed on The Growth Performance and Survival of Catin Fish (Pangasius hypophthalmus) - Hidayatullah, Lalu Rifki; Setyono, Bagus Dwi Hari; Diniariwisan, Damai (Universitas Teuku Umar, 2025)
The purpose of this study was to analyze the effect of exposure to polyvinyl chloride microplastics on the growth and survival rate of catfish (Pangasius hypophthalmus). Microplastics are plastic particles with a diameter of less than 5 mm. The lower limit of particle size included in the microplastic group has not been defined with certainty, but most studies take particle objects with a minimum size of 300 µm3. Microplastics are divided into size categories, namely large (1-5 mm) and small (<1 mm). Polyvinyl Chloride is a plastic that is physically in the form of fine white granules. From its physical properties, PVC is the type of plastic that is most difficult to recycle. Fish farming activities are certainly susceptible to the use of materials containing plastic such as the use of PVC pipes. The presence of microplastics in waters can be eaten by aquatic biota such as fish. The chemical content of plastic will also be absorbed into the bodies of aquatic biota, so that if consumed by humans, toxic transfer will occur. The treatments given in this study were, P1 Without giving microplastics (control), P2 Giving 0.01mg/ 0.75 g of feed, P3 Giving 0.1mg/ 0.75 g of feed and P4 Giving 1mg/ 0.75 g of feed. The method used in this study was a completely randomized design (CRD) method consisting of 4 treatments and 3 replications so that 12 experimental units were obtained. The addition of microplastics to the P4 treatment feed (1 mg/L 0.75 g of feed) showed that catfish experienced a significant effect of microplastic exposure on growth, compared to other treatments.